Athlete assessment and intervention during real competition - Carlstedt, R. A. (The Journal of the American Board of Sport Psychology, 2008)
This presentation which was delivered at the APA 2008 annual convention in Boston reviewed ten years of ambulatory, ecological and longitudinal research of athlete performance, assessment and intervention during real competition and training that was carried out by the author and his students. In addition to select out-takes of data and a discussion of findings research methodologies, procedures and interventions can be viewed through short film clips that are embedded in this PowerPoint. Viewers will also be able to observe ABSP Intern and Visiting Fellows at work with athletes as part of the ABSP summer training and education programs as well as a ABSP Board Certification program candidate as he carries out his final project on telemetry-based EEG and HRV in golfers. The application of advanced approaches to applied sport psychology and use of high-technology monitoring instruments including the NEXUS-32 telemetry EEG system, BioCom Technologies heart rate variabilty hard and software and Brain Resource Company Internet-based neurocognitive test center can also be seen as a validated athlete assessment and intervention program is applied to tennis, baseball and basketball players and golfers.